The predictive role of platelet-to-lymphocyte ratio and systemic immune-inflammation index in young and middle-aged patients with tibial plateau fractures - Zhou, Shaowei; Yang, Xuemei; Hu, Fang; Dong, Xiaomeng; Song, Qingcheng; Yang, Shuhong; Zhang, Yingze (Frontiers in Surgery, 2025)
BackgroundThere is suggestive evidence that the platelet-to-lymphocyte ratio (PLR) and systemic immune-inflammation index (SII) are related to the severity of fracture. The purpose of this study was to investigate the role of PLR and SII in predicting fracture severity in young and middle-aged patients with tibial plateau fractures (TPFs).MethodsA retrospective cohort study involving 229 patients with isolated TPFs was conducted between January 2015 and December 2019. Medical records of hospitalized patients were extracted from the electronic case system. Three experienced orthopedic surgeons classified the imaging data according to the Schatzker classification. All the patients were divided into two groups: group1 consisted of fractures of mild to moderate severity (Schatzker types I-IV), and group2 consisted of fractures of severe severity (Schatzker types V-VI). Platelet, neutrophil, and lymphocyte values at admission were obtained. The PLR = platelet/lymphocyte counts and the SII = platelet × neutrophil/lymphocyte counts were noted. Patients in groups 1 and 2 were statistically compared in terms of PLR and SII value on hospital admission.ResultsThere were significant differences in the blood PLR, SII, Na+ and K+ levels, and neutrophil count between the two groups. According to the receiver operating characteristic (ROC) curve, the cut-off of PLR and SII were 157.9 and 923.9, respectively. Our results showed that high PLR and SII were remarkably associated with the severity of TPFs. The sensitivity was 60% and the specificity was 86.9% when using the PLR ≥ 157.9 to predict the severity of the TPFs whereas the sensitivity was 63.3% and the specificity was 74.4% to predict the severity of TPFs at SII ≥ 923.9. In the multivariate analyses, the high preoperative PLR and SII were identified as independent predictors of severe TPFs.ConclusionsThe PLR and SII are simple and economical biomarkers that require only routine blood tests with low associated costs. They can be calculated directly from platelet, neutrophil, and lymphocyte counts in standard blood routine reports, making them readily accessible and cost-effective tools to predict the severity of tibial plateau fractures.